t-4=-14

Simple and best practice solution for t-4=-14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for t-4=-14 equation:


Simplifying
t + -4 = -14

Reorder the terms:
-4 + t = -14

Solving
-4 + t = -14

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + t = -14 + 4

Combine like terms: -4 + 4 = 0
0 + t = -14 + 4
t = -14 + 4

Combine like terms: -14 + 4 = -10
t = -10

Simplifying
t = -10

See similar equations:

| 4-6(m+2)=-8 | | 3x-2-6x+12+11x= | | 8=3r-5-4 | | 0.7y-2(3-y)=4 | | w*6-2=5 | | 5x^3+2x-3=4x^3+2x-11 | | v-0.6=0.02 | | y-2+5=13 | | 2(n-4)-3=5 | | 5x-3=7x+9 | | 3(x+9)=6(x-3)-9 | | q-1=-0.08 | | 6(x+1)=3(2x+4)-6 | | (2x+14)+(x+34)= | | 7(t-6)+8t=5(3t+4)-9 | | -6x+5+14x-4x= | | 0.05u+27.5=0.6u-11 | | (6x+4)+(7x-2)= | | 5-7=3x-5x | | -2(4s-6)-12=-3(4s+3)-3 | | 2(3h-2)=14 | | 2x-8x=-5 | | 2(x-3)=2x+4 | | -(w+5)=14 | | 9a^3+15a^2-36a=0 | | -3(5s-4)-12=2(9s+7)-2 | | 42x^2-15x-3=0 | | -2(-3x-w)-(2w-6x)= | | 5x^2+6x=12x-9 | | 8(x+2)=8x+16 | | 0.25x+.05(2-x)=.10(37) | | -5(x-4)=40 |

Equations solver categories